2021
DOI: 10.1002/ldr.4088
|View full text |Cite
|
Sign up to set email alerts
|

A novel‐optimal monitoring model of rocky desertification based on feature space models with typical surface parameters derived from LANDSAT_8 OLI

Abstract: Previous studies monitoring the spatial distribution of rocky desertification have used single indices, a comprehensive index, or image classification. However, these approaches could not distinguish between the degrees of rocky desertification as they did not consider various influencing factors and their interactions. To avoid the above shortcomings, this study used the feature space model and seven typical land surface parameters to establish two categories of rocky desertification model: (1) a point-to-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The reduction in farmland area improved farmland management and increased regional gross industrial product, which together with the continuously rising gross domestic product of the tertiary industry caused a positive rocky desertification development 38 . In addition, the Program of Conversion from Cropland to Forest and Grassland had been applied to restore the vegetation ecosystem since 2005, which has contributed to the gradual development of the ecological and environmental conditions of karst rocky desertification in a benign direction 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in farmland area improved farmland management and increased regional gross industrial product, which together with the continuously rising gross domestic product of the tertiary industry caused a positive rocky desertification development 38 . In addition, the Program of Conversion from Cropland to Forest and Grassland had been applied to restore the vegetation ecosystem since 2005, which has contributed to the gradual development of the ecological and environmental conditions of karst rocky desertification in a benign direction 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Since karstic desertification occurs only in karst areas, and there were some non-karst areas in the study area, this study used 1:50,000 lithological vector data (http://www. karstdata.cn/, accessed on 22 June 2022) from Huaxi District to mask non-karst areas before constructing the rocky desertification index model [12]. As the reflectance of rocky areas is similar to that of built-up areas and bare land, it is difficult to distinguish them using the spectral features of the images, which can easily lead to misclassification of rocky desertification [38], so built-up areas and bare land need to be removed before the construction of the rocky desertification supervisory information extraction model; as water bodies are also unlikely to undergo rocky desertification, they also need to be removed.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…Remote sensing technology has gradually become the main means of rocky desertification monitoring because of its ability to obtain large-scale rocky desertification information in a rapid and timely manner and to achieve large-scale rocky desertification monitoring and assessment [8][9][10][11]. Conventional remote sensing image classification methods such as supervised classification and unsupervised classification are highly subjective and have difficulty distinguishing the grade of rocky desertification, cannot directly indicate the development status of rocky desertification, and are not suitable for extracting spatial distribution, area and grade information of rocky desertification [12,13]. The mixed image element decomposition method (SMA) is a relatively common method in the study of karst desertification, but due to the discontinuous distribution of topography in karst areas and the influence of human activities, weathering and erosion, end element variation is common and it is very difficult to obtain feature end elements, so the SMA method cannot easily obtain information on rocky desertification [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normalized difference vegetation index (NDVI), a key product from MODIS or other remote sensing data, has a high positive correlation with vegetation coverage, suggesting an effective basis for KRD mapping (Li & Wu, 2015; Zhang et al, 2017). One case study showed that as KRD intensity decreases, NDVI increases (Chen et al, 2014; Guo et al, 2021). Yet, NDVI within the same rocky desertification level tends to fluctuate over a large range of values (Chen et al, 2014; Zhu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%